Serum transferrin as a predictor of prognosis for hepatic arterial infusion chemotherapy in advanced hepatocellular carcinoma. Issue 5 (22nd May 2013) - Zaitsu, Junichi; Yamasaki, Takahiro; Saeki, Issei; Harima, Yohei; Iwamoto, Takuya; Harima, Yumiko; Matsumoto, Toshihiko; Urata, Yohei; Hidaka, Isao; Marumoto, Yoshio; Ishikawa, Tsuyoshi; Takami, Taro; et al.
<x xml:space="preserve">Abstract</x> Aim We recently reported that the iron chelator deferoxamine (DFO) is efficacious in advanced hepatocellular carcinoma (HCC) patients. Iron regulation may thus have an important impact in HCC therapy. Because transferrin is a native chelator that regulates iron homeostasis, it may act as an anticancer agent in a similar manner as DFO. The objective of this study was to evaluate serum transferrin as a prognostic predictor in advanced HCC patients undergoing hepatic arterial infusion chemotherapy (HAIC). Methods We retrospectively studied 44 patients receiving HAIC and analyzed various parameters for their possible use as prognostic predictors. Results The 1‐, 2‐ and 3‐year cumulative survival rates were 36.4%, 18.2% and 8.5%, respectively, and the median survival time (MST) was 7.0 months. The survival rates of patients who had serum transferrin of 190 mg/dL or more (MST, 12.0 months) were significantly better than those of patients who had serum transferrin of less than 190 mg/dL (MST, 4.9 months). Multivariate analysis identified serum transferrin of 190 mg/dL or more (hazard ratio [HR], 0.282; 95% confidence interval [CI], 0.132–0.603; P = 0.001) and Child–Pugh score B (HR, 1.956; 95% CI, 1.034–3.700; P = 0.039) as independent prognostic predictors. There was a significant correlation between serum transferrin level and therapeutic effect (P < 0.001). Conclusion Serum transferrin could be useful as a prognostic predictor in advanced HCC patients before HAIC treatment.